Asymmetric Carboxycyanation of Aldehydes by Cooperative AlF/Onium Salt Catalysts: from Cyanoformate to KCN as Cyanide Source. Issue 6 (2nd January 2019) - Brodbeck, Daniel; Álvarez‐Barcia, Sonia; Meisner, Jan; Broghammer, Florian; Klepp, Julian; Garnier, Delphine; Frey, Wolfgang; Kästner, Johannes; Peters, René
Abstract: Asymmetric 1, 2‐additions of cyanide yield enantioenriched cyanohydrins as versatile chiral building blocks. Next to HCN, volatile organic cyanide sources are usually used. Among them, cyanoformates are more attractive on technical scale than TMSCN for cost reasons, but catalytic productivity is usually lower. Here, the development of a new strategy for cyanations is described, in which this activity disadvantage is overcome. A Lewis acidic Al center cooperates with an aprotic onium moiety within a remarkably robust bifunctional Al–F–salen complex. This allowed for unprecedented turnover numbers of up to 10 4 . DFT studies suggest an unexpected unique trimolecular pathway in which the ammonium bound cyanide attacks the aldehyde, which itself is activated by the carbonyl group of the cyanoformate binding to the Al center. In addition, a novel practical carboxycyanation method was developed that makes use of KCN as the sole cyanide source. The use of a pyrocarbonate as carboxylating reagent provided the best results. Abstract : Trimolecular? The evolution of a robust, highly active catalyst for asymmetric aldehyde cyanations is reported, which in the final synthetic protocol uses inorganic KCN instead of volatile organic cyanation reagents. DFT studies for the initial protocol using a cyanoformate reagent suggest a unique trimolecular reaction pathway.